UTILIZATION OF THOMAS MODEL TO PREDICT THEBREAKTHROUGH CURVES FOR ADSORPTION AND IONEXCHANGE (Journal of Engineering, 2024)
Fixed bed sorption processes such as adsorption and ion exchange do not operate at steady state. The design equations are differential that usually require numerical methods to solve. Thomas gives a general analytical solution for these equations. It is based on second-order reaction kinetics and the assumption of Langmuir isotherm. Computer program for the solution of Thomas model was designed using MATLAB 7.0. Four sets of experimental data are tested to show the capability of Thomas model to predict the breakthrough curves for adsorption and ion exchange processes. These data represent the sorption of o-cresol from water by activated carbon, acetic acid from air by activated carbon, phenol from water by natural zeolite, and trichloroethylene from air by zeolite- 5A.The results show that there are a good agreement between the experimental data and the model.